BUDAYA TEKNOLOGI PEMBUATAN PERAHU TRADISIONAL DI SULAWESI SELATAN (Forum Ilmu Sosial, 2011)
This study is an attempt to understand and explain cultural phenomena in the tradition of boat building that became a part of life of most people in South Sulawesi. Siriâ€™ value system â€˜ can motivate people to dare to do high risk jobs such as sailing on the ocean, or motivate people to excel in mastering the science of the sea, and motivate people to master technology in boat building. The problems posed here are: (1) How the process of making traditional boats were cultivated by the people in South Sulawesi?; (2) Who were the actors in the process of acculturation of technology in making the boat?The purpose of this research is to try to understand and explain how the traditional boat-making process by the people of South Sulawesi. The study also sought to understand and explain any actor in the process of making the boat. The method used here is a qualitative research method, while the data collection techniques is done by observation and in-depth interviews. Research sites are in District Takalar and Bulukumba in South Sulawesi Province. The results of this study indicate that, in the process of boat building,people still pay attention to the tradition, where the boat launch begins with prayers. This ritual is usually at the time of installation of the wooden keel boat that serves as the foundation of the ship. At the time of the launch of the ship into the water, it is usually preceded by a specifc ritual and barzanji. In addition, an infuential actor in the acculturation of traditional boat technology is the Ponggawa and the buyer who will buy the ship. Konjo tribe which is a sub-tribe of the famous Bugis is society as a maker of traditional boats in South Sulawesi.Â